Fundraising principles and practice - Sargeant, Adrian; Shang, Jen, 1979- (Hoboken : Wiley, 2017)
"The complete guide to fundraising planning, tools, methods, and more Fundraising Principles and Practice provides a unique resource for students and professionals seeking to deepen their understanding of fundraising in the current nonprofit environment. Based on emerging research drawn from economics, psychology, social psychology, and sociology, this book provides comprehensive analysis of the nonprofit sector. The discussion delves into donor behavior, decision making, social influences, and models, then uses that context to describe today's fundraising methods, tools, and practices. A robust planning framework helps you set objectives, formulate strategies, create a budget, schedule, and monitor activities, with in-depth guidance toward assessing and fine-tuning your approach. Coverage includes online fundraising, major gifts, planned giving, direct response, grants, corporate fundraising, and donor retention, with an integrated pedagogical approach that facilitates active learning. Case studies and examples illustrate the theory and principles presented, and the companion website offers additional opportunity to deepen your learning and assess your knowledge. Fundraising has become a career specialty, and those who are successful at it are among the most in-demand in the nonprofit world. Great fundraisers make an organization's mission possible, and this book covers the essential information you need to help your organization succeed. Adopt an organized approach to fundraising planning Learn the common behaviors and motivations of donors Master the tools and practices of nonprofit fundraising Manage volunteers, monitor progress, evaluate events, and more Fundraising is the the nonprofit's powerhouse. It's the critical component that supports and maintains all activities, and forms the foundation of the organization itself. Steady management, clear organization, effective methods, and the most up-to-date tools are vital to the role, and familiarity with donor psychology is essential for using these tools to their utmost capability. Fundraising Principles and Practice provides a comprehensive guide to all aspects of the field, with in-depth coverage of today's most effective approaches"--
"Fundraising Principles and Practice 2e is based on an emerging body of fundraising research drawn from the domains of economics, psychology, social psychology and sociology. It summarizes and interprets this research to explore its implications for modern fundraising practice. It also provides numerous case studies and examples to illustrate the theory and principles that it explains. What sets this book apart from is there is no other formal textbook with an integrated pedagogical approach to ensure student learning. This is also the only text to have an associated website (www.studyfundraising.info) where students can deepen their learning and assess their knowledge"--
Introduction to the Nonprofit Sector -- The Development of a Profession -- Fundraising Ethics -- Individual Giving Behavior -- Social Influences on Giving -- Fundraising Planning: The Fundraising Audit -- Fundraising Planning -- Case for Support -- Assessing Fundraising Performance -- Direct Response Fundraising -- Digital Fundraising / Adrian Sargeant, Steven Shattuck -- Social Media / Steven Shattuck, Adrian Sargeant -- Donor Retention and Development -- Major Gift Fundraising / Robert F Hartsook, Adrian Sargeant -- Bequest, In Memoriam, and Tribute Giving / Claire Routley, Adrian Sargeant -- Planned Giving / Matthew J Beem, Adrian Sargeant -- Corporate Giving and Fundraising -- Grant Fundraising -- Fundraising Events / Karin L Cox -- Managing Fundraising Volunteers / Walter Wymer, Adrian Sargeant -- Leading Fundraising Teams -- Managing Public Trust and Confidence.
Revised edition of the authors' Fundraising principles and practice, c2010.
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and indexes.
John Wiley and Sons
Keywords: Fund raising; Nonprofit organizations -- Finance; Nonprofit organizations -- Marketing; Collecte de fonds; Associations sans but lucratif -- Finances; Associations sans but lucratif -- Marketing; fund raising; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Fund raising; Nonprofit organizations -- Finance; Nonprofit organizations -- Marketing